Incidence of Invasive Fungal Infections in Patients With Previously Untreated Acute Myeloid Leukemia Receiving Venetoclax and Azacitidine. (24th September 2022) - Zhang, Alexander; Johnson, Tanner; Abbott, Diana; Phupitakphol, Tanit; Gutman, Jonathan A; Pollyea, Daniel A; Koullias, Yiannis
Abstract: Background: Acute myeloid leukemia (AML) is associated with poor prognosis, particularly in elderly patients with comorbidities. Combining azacitidine (AZA) with BCL-2 inhibitor venetoclax (VEN) demonstrated significant improvement in outcomes for newly-diagnosed AML patients compared to AZA alone. However, this regimen is myelosuppressive, and the incidence of invasive fungal infections (IFIs) and impact of antifungal prophylaxis are not well defined. Methods: This retrospective cohort study evaluated newly-diagnosed AML patients treated with VEN/AZA at the University of Colorado Hospital from January 2014 to August 2020. Patients with history of prior IFI were excluded. Primary outcome was IFI incidence during VEN/AZA therapy. χ 2 and Fisher exact tests assessed the impact of patient demographics, AML-specific risk factors, and receipt of antifungal prophylaxis on IFI incidence. Results: 144 VEN/AZA-treated AML patients were included in the study. 25 (17%) patients developed IFI: 8% (n = 2) "proven, " 24% (n = 6) "probable, " and 68% (n = 17) "possible" per European Organization for Research and Treatment of Cancer and the Mycoses Study Group Education and Research Consortium criteria. There was no statistically significant association between IFI incidence with age, sex, or European LeukemiaNet classification. 10 patients received antifungal prophylaxis; none developed IFI. IFI incidence rate per 1000 patient-days was greatest 0–9 days after starting VEN/AZA, at 8.39. Conclusions: Incidence of "proven" and "probable" IFI in our VEN/AZA-treated AML cohort was 5.6%, in-line with incidence rates reported by recent similar studies. Furthermore, IFI incidence decreased as days from starting VEN/AZA therapy increased.